Generalized frequency weighted optimal Hankel norm model reduction - Kumar D.; Nagar S.K. (My University, 2025)
This paper presents a generalized frequency weighted optimal Hankel norm model reduction (GFWOHNMR) technique. The proposed algorithm is an extension of approach discussed in [9] and results stable reduced order models with both single sided and double sided weightings. A numerical example is considered to validate the proposed algorithm. © 2013 IEEE.